Playground slide-related injuries in preschool children: increased risk of lower extremity injuries when riding on laps - Charles A. Jennissen; Maggie Koos; Gerene Denning (BMC, 2018)
Abstract Background The purpose of this study was to better understand the factors associated with playground slide-related injuries in preschool children and to test the hypothesis that riding on laps increases the likelihood of lower extremity injuries. Methods Playground slide-related injuries (product code 1242) in children ≤5 years of age treated in emergency departments from 2002 to 2015 were identified (N = 12,686) using the U.S. Consumer Product Safety Commission's National Electronic Injury Surveillance System (NEISS). Descriptive and comparative analyses, including chi-square testing and binary logistic regression, were performed. Results Based on NEISS stratified national sampling estimates, over 350,000 children ≤5 years of age were injured on slides from 2002 to 2015. Overall, 59% of the children were male, and 65% were white. Almost 60% of injuries occurred in parks or other public areas. The most frequent diagnosis was a fracture (36%); lacerations were 19% of the injuries. A higher proportion of musculoskeletal injuries were seen in toddlers < 3 years old as compared to those 3-5 years of age (p < 0.001). Injuries to the lower extremities increased in frequency as age decreased, whereas injuries to the upper extremities and head/neck/face were more common in older preschoolers. Children < 3 years of age were 12 times more likely to be identified from narratives as being on another person's lap at the time of injury. Children identified as being on a lap had an increased odds of injury to the lower extremity than to other body parts (OR 43.0, 95% confidence interval (CI) 32.0-58.0), and of lower leg/ankle fracture than fractures elsewhere (OR 49.5, 95% CI 31.7-77.4). Conclusions Decreasing age was associated with a higher likelihood of being identified as sliding down on another person's lap and a higher likelihood of lower extremity injuries. Healthcare providers should be mindful of the potential for these slide-related injuries as they can result in a toddler's fracture of the tibia, which may be occult. Parents should also be made aware of this increased risk and counseled that a child's foot can catch on the slide's surfaces when going down on a person's lap with subsequent twisting forces that can result in a fracture.